Strategy of the Regional Financial and Asset Management Agency in Increasing Bima City's Original Regional Income - Fadila, Nurul; Mustamin, Mustamin; Rifaid, Rifaid; Kusuma, Bayu Mitra A. (Department of Government Studies, Universitas Syiah Kuala, 2024)
This research aims to analyze the Strategy of the Regional Financial and Asset Management Agency in Increasing Bima City's Original Regional Income. The research method used in this research is descriptive qualitative. The research results show the strategy of the Regional Financial and Asset Management Agency in an effort to increase Regional Original Income, namely the strategy set by the Regional Financial and Asset Management Agency in increasing Regional Original Income is Intensity and Assistance where the Regional Financial and Asset Management Agency must first strengthen all forms of regulations regions related to their Regional Original Income as a reference in determining them. Carrying out data collection on all tax objects because some have already been recorded, but if there is a change in the value, the Regional Financial and Asset Management Agency automatically has to re-register the data again. Carrying out audits of taxpayers, namely issuing letters regarding tax assessments for collection. If there is no response from the taxpayer, they will carry out an inspection. Creating a digital channel called Regional Tax Transaction Electronification to make it easier and help the community, but unfortunately this strategy is still in process and has not yet been realized.